Metodologia para avaliação das consequências da expansão dos sistemas elétricos nos sistemas de aterramento das subestações - Rosa, Wagner (2022)
Factors such as economic growth, population growth and changes in consumption habits lead to a constant increase in electricity consumption levels. This constant increase in consumption makes it necessary to routinely expand generation, transmission and distribution systems in order to meet this growing demand. This routine expansion of electrical systems alters the characteristics of the system itself, thus altering power flows and short-circuit levels. These changes can lead certain systems to overcome, being necessary to carry out some intervention in order to endow these systems with the characteristics necessary for full operation in the new required conditions. One of the systems that end up, many times, being overcome is the grounding systems of the substations. Considering that these systems have a function related to the safety of people, it is very important to monitor and study the impacts of the expansion of electrical systems with regard to grounding systems, in addition to developing a methodology for carrying out a diagnosis of the condition of the grids. Existing. As it was impossible to measure the soil resistivity on the plateaus of existing and operating substations, measurements were carried out on land in the vicinity of a recently built substation, of which all the design elements were known, with the objective of verifying whether the Resistivity measurement in the vicinity of a substation can be considered representative for the substation in question. Subsequently, this method was replicated for an old substation. The field surveys and the treatment of the data obtained in these surveys served to determine the mesh resistance of the substations. In order to verify the overcoming of the grounding system of a substation, it is necessary to know, in addition to the grounding resistance, the entire grounding system of that substation, the distribution of the fault current in the different parts of this system and the mesh current, being the current of mesh responsible for the step and touch voltages along the substation plateau. In order to determine the mesh current, the grounding systems of these substations were modeled in the EMTP/ATP, including the grounding of the transmission lines connected to the substations of interest, since their guard cables and towers are part of the substations grounding system. The measurement around the substation proved to be representative of the plateau and, therefore, can be used when there is no record of measurements from the design phase. In turn, the modeling of the substation grounding system in EMTP/ATP proved to be a very effective way to determine the mesh current. With the determination of the mesh currents of the substations of interest, it was possible to verify the overcoming of the mesh of one of the substations. The initial propositions of this work sought to verify the impacts of the constant expansions of the electrical systems for the earth grids of the substations and the development of a methodology for the verification of possible overruns in old substations, and it is possible to understand that the objectives were met.